2017
DOI: 10.1162/jocn_a_01022
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Standard Neural Signature of the Word–Nonword Distinction

Abstract: The distinction between letter strings that form words and those that look and sound plausible but are not meaningful is a basic one. Decades of functional neuroimaging experiments have used this distinction to isolate the neural basis of lexical (word-level) semantics, associated with areas such as the middle temporal, angular, and posterior cingulate gyri that overlap the default-mode network. In two functional magnetic resonance imaging (fMRI) experiments, a different set of findings emerged when word stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 71 publications
8
34
1
Order By: Relevance
“…In humans, real words typically result in more activation than pseudowords, evoking activity in what has been called a general semantic network ( Binder et al, 2009 ). Although such activations are generally bilateral, they tend to lateralize more to the left and cluster around the angular gyrus, but that anatomical location is ill-defined and is sometimes called the TPJ or temporal-parietal-occipital cortex (TPO) ( Graves et al, 2017 ). It is clear that the nature of the task and the relative frequency of words and pseudowords can influence the relative activation to words and pseudowords.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, real words typically result in more activation than pseudowords, evoking activity in what has been called a general semantic network ( Binder et al, 2009 ). Although such activations are generally bilateral, they tend to lateralize more to the left and cluster around the angular gyrus, but that anatomical location is ill-defined and is sometimes called the TPJ or temporal-parietal-occipital cortex (TPO) ( Graves et al, 2017 ). It is clear that the nature of the task and the relative frequency of words and pseudowords can influence the relative activation to words and pseudowords.…”
Section: Discussionmentioning
confidence: 99%
“…1 with Fig. 2 A , a binarized version of nonword activations from Graves et al 2017 , their Fig. 1 A ).…”
Section: Methodsmentioning
confidence: 99%
“…But we also know that differences in task difficulty can influence results that depend on contrasting different task conditions. Indeed, a recent study demonstrated a new level of influence of task difficulty effects, where differences in task difficulty led to a reversal of the typical pattern of activation for contrasting meaningful words and meaningless nonwords ( Graves et al 2017 ). Areas that typically respond to semantic information were found to activate more for meaningless nonwords than meaningful words.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations